2002
DOI: 10.1007/pl00012667
|View full text |Cite
|
Sign up to set email alerts
|

Two herbivore-deterrent iridoid glycosides reduce the in-vitro growth of a specialist but not of a generalist pathogenic fungus of Plantago lanceolata L

Abstract: Many secondary plant compounds are involved in defense against both insect herbivores and pathogens. Two secondary plant compounds of Plantago lanceolata, the iridoid glycosides catalpol and its precursor aucubin, are well known for their deterrent effects on generalist and nonadapted specialist insect herbivores. We tested the effects of these compounds on the in-vitro growth of a specialist and generalist fungal pathogen of this host species. Two chemical forms of these iridoids were tested. The glycosides a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 36 publications
1
42
0
Order By: Relevance
“…larvae, Elateridae) on secondary plant chemistry of two full-sib families of Plantago lanceolata (Plantaginaceae) from lines that were selected for low and high levels of defensive compounds (iridoid glycosides [IG]). IG are known to deter generalist insect herbivores (Bowers and Puttick 1988) and pathogens (Marak et al 2002a). However, they are used as feeding and oviposition stimulants by specialist herbivores (Bowers 1983).…”
Section: Introductionmentioning
confidence: 99%
“…larvae, Elateridae) on secondary plant chemistry of two full-sib families of Plantago lanceolata (Plantaginaceae) from lines that were selected for low and high levels of defensive compounds (iridoid glycosides [IG]). IG are known to deter generalist insect herbivores (Bowers and Puttick 1988) and pathogens (Marak et al 2002a). However, they are used as feeding and oviposition stimulants by specialist herbivores (Bowers 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have documented genetic variation in IG levels within and among populations of P. lanceolata (Bowers andStamp 1992, 1993;Adler et al 1995). Marak et al (2000) have estimated a realized heritability (Ϯ SE) of leaf IG concentrations in P. lanceolata of 0.23 Ϯ 0.07. The deterrent effects of aucubin and catalpol on pathogens (Rombouts and Links 1956;Marak et al 2002) and generalist insect herbivores of P. lanceolata (Bowers and Puttick 1988;Bowers 1991) are well documented.…”
mentioning
confidence: 99%
“…Marak et al (2000) have estimated a realized heritability (Ϯ SE) of leaf IG concentrations in P. lanceolata of 0.23 Ϯ 0.07. The deterrent effects of aucubin and catalpol on pathogens (Rombouts and Links 1956;Marak et al 2002) and generalist insect herbivores of P. lanceolata (Bowers and Puttick 1988;Bowers 1991) are well documented. By contrast, specialist insects can use these compounds as feeding and oviposition stimulants (Pereyra and Bowers 1988;Klockars et al 1993) and sequester them for their own defense against predators and parasitoids (Dyer and Bowers 1996;Camara 1997;Suomi et al 2001).…”
mentioning
confidence: 99%
“…methanol, then filtered and diluted 10 times with ultrapure water. The concentration of the IGs aucubin and catalpol were analyzed using HPLC as described by Marak et al (2002b). Due to practical limitations, leaf and root chemistry could only be determined for a subset of the treatments.…”
Section: Plants and Insectsmentioning
confidence: 99%
“…Moreover, these compounds affect the performance of both plant-beneficial and plant-pathogenic fungi (Marak et al 2002b;Biere et al 2004;De Deyn et al 2009). Several studies have shown that iridoid glycoside concentrations can increase in response to damage by aboveground (e.g.…”
Section: Introductionmentioning
confidence: 99%